Hubungan Pola Makan dengan Kekurangan Energi Kronik (KEK) Menggunakan Pengukuran Lila pada Ibu Hiperemesis Gravidarum di Wilayah Kerja Puskesmas Maluk Kabupaten Sumbawa Barat - Endy Bebasari Ardhana Putri; Riska Oktaviana; Nurhidayah Nurhidayah; Hadi Suryatno (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2023)
Introduction : Hyperemesis gravidarum (HG) is a pregnancy complication characterized by continuous nausea and vomiting, wich results in chronic loss and chronic energy deficiency in pregnant women. Purpose : To determine whether there is a correlation between diet and Chronic Energy Deficiency (KEK) LILA measurements will be used in pregnant women with hyperemesis gravidarum in the working area of UPTD Maluk Helath Center, West Sumbawa Regency, in 2023. Method : The research method used for this study is cross-sectional analysis. The population in this study included all pregnant women whit hyperemesis gravidarum from July to Desember 2022, totaling 58 respondents. This sample size onsisted of 58 respondents, utilizing the total sampling technique. Data analysis was conducted using the chi-square test with the assistance of SPSS version 25.0. the research instrument employed was a questionnaire. Result : Of the 58 population, 8 (13.8%) respondents did not experience CED by looking at the correct eating patterns of 1 (12.5%) respondents, less precisely 7 (87.5%) respondents. Meanwhile, 50 (86.2%) respondents experienced CED with the correct eating pattern of 1 (2%) respondent, 17 (34%) respondents not quite correct, 32 (64%) respondents incorrectly. Based on statistical analysis, the p value is 0.002 (<0.05) so Ha is accepted. Conclusion : There was relationship between diet and Chronic Energy Deficiency (CED) using LILA measurements in mothers with hyperemesis gravidarum.